(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
A review of the bibliography coupled with the Authors’ personal experience shows that drawing, as a technique for recording serial transverse sections of Brachiopods is inadequate and inaccurate. Especially structures such as the brachidium, septalium, but also cardinalia, even in optimal state of preservation can be drawn only imprecisely: more so where diagenesis has occurred. Further, drawing always involves filtering data, thus altering the original information. For this reason we are opting for photography as a far truer and more accurate technique than drawing for recording serial transverse sections of the internal structures of Brachiopoda.